Myths in myopia epidemiology and treatment - Lança, Carla (2024)
Practicing evidence-based medicine requires constant effort to acquire, assess, and implement new knowledge that improves our care. Since 2013, more than 1000 publications per year have discussed myopia,1 many challenging existing medical beliefs. As in other areas of medicine, ophthalmologists are expected to translate new knowledge into their clinical practice as well as manage their demanding clinical schedule. However, practicing clinicians, including ophthalmologists, are sometimes slow to discard medical myths contradicted by available evidence. This is especially true in fields with rapidly evolving research, such as myopia. The goal of this viewpoint is to highlight examples of common beliefs about myopia epidemiology and control that are not evidence-based and to consider corrective educational strategies.